Investigation of the economic impact of different patterns of medication monitoring in general practices - Berdunov, Vladislav (2016)
Medication monitoring is used in primary care to guide treatment and protect the patient from adverse drug events (ADEs). Early detection of ADEs may prevent their development and avoid serious or permanent effects to patient health. Published guidelines for the conduct of medication monitoring in UK primary care recommend monitoring in patients with long-term prescription of certain cardiovascular medications, including angiontensin-converting enzyme inhibitors (ACEI), loop diuretics and amiodarone. Although much evidence exists on the practice of monitoring of these medications in primary care, few studies have considered the effect of carrying out monitoring at different frequencies during long-term therapy on the risk of ADEs. Similarly, evidence of the economic effect of regular monitoring of these medications is sparse. As a consequence, policy-makers rely primarily on evidence from expert opinion as a basis for recommendations and compliance to guidelines in practice is poor. This programme of research aimed to gain an understanding of the nature of monitoring of ACEI, loop diuretics and amiodarone in primary care in England, and investigate the effectiveness and cost-effectiveness of monitoring in accordance with current guidelines.